Group formation as a mechanism for integrating smallholder farmers and development organisations into the cassava value chain: Evidence from Siaya County, Kenya - Florence Achieng Opondo; Poti Owili Abaja; Kevin Okoth Ouko (Cogent Business & Management, 2023)
Underutilized crops play an important role in sustainable food systems, especially in drought-stricken areas occasioned by climate change. These crops, particularly cassava have become a priority in Siaya County, Kenya. This is because of its adaptive nature in the region and its contribution to sustainable food systems. Therefore, both the government and other development bodies have initiated programs to support the development of the cassava value chain while introducing it to mainstream farming systems. Most of these programs have targeted farm-based groups as entry points. However, there is still weak integration between small-scale cassava farmers and development organizations resulting in low performance of the sector. Therefore, this study aims at understanding the framework in which farmer groups are formed and how they are coordinated to link farmers to development organizations. The study adopted a qualitative approach design whereby key informant interviews and focus group discussions were conducted in Siaya County. Data was recorded, transcribed and analysed using ATLAS.ti. software. The results show that most of the farmer groups are just entities sampled together simply because most development organizations use them as entry points. However, there are minimal investments in these groups in terms of capacity development to spearhead cassava value chain development. Notably, most organizations push their agenda through these groups leading to the failure of the programs initiated. Therefore, there is a need to organize the farmer groups into economic entities, sensitize the members on the importance of groups and engage the county agricultural officers when collaborating with development organizations.
Keywords: 650; cassava; groups; integration; organizations; value chain